2019
DOI: 10.1002/eqe.3238
|View full text |Cite
|
Sign up to set email alerts
|

Seismic fragility assessment of nonstructural components in unreinforced clay brick masonry buildings

Abstract: The results of an investigation of the probability of earthquake damage to nonstructural unreinforced masonry (URM) components are presented. The components include parapets, chimneys, and out-of-plane loaded facades typical of low-rise pre-1940 construction in Australia and New Zealand. The study is based on a street survey of component geometry, in situ data on material strength, and simplified mechanical models. Uncertainties in capacity and demand were quantified based on, respectively, stochastic and dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…For lighting fixtures, diagonal braces are not typically deployed; thus, the suspension configuration is the same as that in the "AC w/o brace" configuration, except that there are only two suspension bars. The horizontal stiffness can be calculated following Equations (11) and (12).…”
Section: Lighting Fixturementioning
confidence: 99%
See 2 more Smart Citations
“…For lighting fixtures, diagonal braces are not typically deployed; thus, the suspension configuration is the same as that in the "AC w/o brace" configuration, except that there are only two suspension bars. The horizontal stiffness can be calculated following Equations (11) and (12).…”
Section: Lighting Fixturementioning
confidence: 99%
“…Observations of the damage suffered by nonstructural components vary with the architectural style, and the damage can be categorized into two groups, ie, drift sensitive and acceleration sensitive . The failure of suspended ceiling systems, which is acceleration sensitive, is among the most commonly reported sources of damage .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that the developed data provide a realistic estimate of non-structural component seismic performance (Derakhshan et al 2019). Pardalopoulos and Pantazopoulou investigated the seismic response of non-structural elements attached on multi-storey.…”
Section: Introductionmentioning
confidence: 99%
“…The suspended ceilings are susceptible to damage and failure when buildings are subjected to earthquake‐induced strong ground motions, which leads to immeasurable economic loss and hinders the timely rescue of the injured 1–3 . For example, the 1989 Loma Prieta earthquake highlighted the severe collapse and failure of massive ceiling panels in the San Francisco International Airport due to the collision between light fixtures and ceiling runners.…”
Section: Introductionmentioning
confidence: 99%